Clinical case of oropharyngeal metastasis of kidney cancer - Т. А. Aketova; R. I. Azizyan; S. D. Bezhanova; А. А. Zotova; V. Zh. Brzhezovskiy (Опухоли головы и шеи)
Oropharyngeal metastases are very rare and occur in approximately 1.0–1.5 % of all malignant tumors of the oral cavity and oropharynx. Information on oropharyngeal localization of metastases of kidney cancer is almost absent in the literature. A description of a rare clinical observation of metastasis of clear cell renal cell carcinoma into the oropharynx is presented.